Risk management in short–term rental properties: methods and strategies for minimizing risks - N. O. Berezovskaia (Путеводитель предпринимателя, 2024)
This article aims to identify and analyze effective risk management strategies within the short–term rental market, focusing on enhancing operational efficiency and profitability while ensuring compliance and security. The study utilizes a methodological framework that integrates data–driven risk assessments, optimization of rental strategies through predictive analytics, the implementation of advanced security systems, and rigorous regulatory compliance. Key findings demonstrate that these strategies significantly mitigate financial, operational, and legal risks, contribute to sustainable business practices, and enhance the market reputation of property managers. The conclusion underscores the necessity of incorporating technological advancements and stringent compliance measures as foundational elements of modern property management. The novelty of this work lies in its comprehensive approach to integrating diverse risk management strategies, providing a holistic view that addresses the multifaceted challenges faced by today’s short–term rental businesses.